Recurrent Bartholin's Cyst: Literature Review and Case Report - Shariff, Fonda Octarianingsih; Septian, Diki; Fajarwati, Dinda Dwi; Siagian, Ellys Tahnia; Lasmawati, Eggy; Aprillya, Eva; Hanifa, Fidati; Lawren, Jeane (Muhammadiyah Medical Journal, 2022)
Bartholin's cyst is a form of cystic (fluid-filled) tumor on the vulva. Bartholin's cyst is a cyst that forms due to blockage of the Bartholin's gland duct, which causes retention and cystic dilatation. Reports indicate that a 45-year-old woman came to the Obstetrics and Gynecology Polyclinic at Pertamina Bintang Amin Hospital, Malahayati Bandar Lampung, experiencing a recurrence of a left Bartholini abscess for the third time after two external incisions. The treatment carried out in this patient was given antibiotics and analgesics and it was recommended to do surgery with an extirpation procedure. Recurrent Bartholin's gland abscesses in women of reproductive age are generally associated with a risk of contact with sexually transmitted infection polymicrobials. Needle aspiration and incision and drainage are the two simplest procedures, not recommended because of the relatively increased recurrence rate.